2006
DOI: 10.1614/ws-06-004r.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed diversity and soybean yield with glyphosate management along a north–south transect in the United States

Abstract: There are many concerns about the effects of repeated use of glyphosate in glyphosate-resistant (GR) crops, including two that are seemingly contradictory. These are (1) weed escapes and (2) loss of weed diversity. Weeds that escape glyphosate treatment represent species that likely will become troublesome and difficult to control in the future, and identifying these future problems may allow more effective management. In contrast, complete weed control directly reduces the weed component of agroecosystem biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
2
24
0
1
Order By: Relevance
“…Such occurrence has been considered abnormal and could be associated with alterations of the soybean production system. Among the factors probably favoring the occurrence of mites are the use of new soybean cultivars, with favorable nutritional and morphological composition (Elden, 1997;Ali, 1999;Abraham, 2000;Rita & Lajos, 2001), increased use of glyphosate, which may reduce the biological diversity of the system and affect the arthropod population (Buckelew et al, 2000;Bitzer et al, 2002;Scursoni et al, 2006) and can be detrimental to entomopathogenic fungi (Morjan et al, 2002), pesticide use for pest management, which can influence, directly and indirectly, the spider mite population (Gerson & Cohen, 1989;Trichilo & Wilson, 1993;Grout et al, 1997;Childers & About-Setta, 1999;Sato et al, 2001Sato et al, , 2002James, 2003;Beers et al, 2005;Prischmann et al, 2005), and the occurrence of droughts (Flechtmann, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Such occurrence has been considered abnormal and could be associated with alterations of the soybean production system. Among the factors probably favoring the occurrence of mites are the use of new soybean cultivars, with favorable nutritional and morphological composition (Elden, 1997;Ali, 1999;Abraham, 2000;Rita & Lajos, 2001), increased use of glyphosate, which may reduce the biological diversity of the system and affect the arthropod population (Buckelew et al, 2000;Bitzer et al, 2002;Scursoni et al, 2006) and can be detrimental to entomopathogenic fungi (Morjan et al, 2002), pesticide use for pest management, which can influence, directly and indirectly, the spider mite population (Gerson & Cohen, 1989;Trichilo & Wilson, 1993;Grout et al, 1997;Childers & About-Setta, 1999;Sato et al, 2001Sato et al, , 2002James, 2003;Beers et al, 2005;Prischmann et al, 2005), and the occurrence of droughts (Flechtmann, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, a 2‐yr study along a 1600 km north–south gradient in the US, showed differences in weed diversity between single application glyphosate treatments and weedy controls in different locations between years reflecting temporal variance (Scursoni et al. ). In the current study, there was a clear distinctiveness of comparatively homogeneous weed communities associated with each hardiness zone consistent through 5 yr of observation.…”
Section: Discussionmentioning
confidence: 99%
“…), but are likely to have affected weed communities secondarily to location (Scursoni et al. ). In only 2 of 5 yr did crop rotation affect floristic similarity of the weed communities among sites, and GR trait rotations showed no effect in any year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are in line with the findings by Smith & Gross (2007), who found that the effects of annual crop diversity on weed communities were dependent on the crop rotation phase, and across all phases of rotation, weed community structure was affected more by crop identity than crop diversity per se. After releves made in experiments planted along a transect in the US corn belt, Scursoni et al, (2006) also suggest that higher weed diversity can be maintained with the use of a single application …”
Section: Diversitymentioning
confidence: 99%